(untitled) (Mustansiria Dental Journal, 2018)
Aim: The present study compares the accuracy of conventional and digital radiographic system in the determination of apical fitness in endodontic therapy. Method: Thirty three root canals of first upper and lower molar teeth were used in this study; a K-file was inserted into the canal until its tip was fit snuggly one millimeter shorter than the apex. Each tooth was radiographed twice with two different radiographic systems; conventional & digital systems. The right-angle paralleling technique with film holders was used in both systems. The distance between the file tip and the center of radiographical apex from both imaging systems was measured by two examiners and the mean of each two measurements was recorded, the data was collected and analyzed statistically by paired t- test. Results: The mean value of radiographic length reveals that there is a very small difference between the measurements of conventional radiographic system (0.8727mm) and those measurements of digital radiographic system (0.8367mm) when compared with the real length measurements (1mm). Paired t-test shows that there is no significant difference (p < 0.05) was founded between the real measurements and the radiographic measurements are taken from both conventional and digital systems. In conclusion both the conventional and digital imaging systems can be used accurately for working length determination in an endodontic therapy.